Overlapping CNS inflammatory diseases: differentiating features of NMO and MS. Issue 1 (23rd September 2014) - Juryńczyk, Maciej; Craner, Matthew; Palace, Jacqueline
Abstract : Neuromyelitis optica (NMO) has long been considered as a variant of multiple sclerosis (MS) rather than a distinct disease. This concept changed with the discovery of serum antibodies (Ab) against aquaporin-4 (AQP4), which unequivocally differentiate NMO from MS. Patients who test positive for AQP4-Abs and present with optic neuritis (ON) and transverse myelitis (TM) are diagnosed with NMO and those who show an incomplete phenotype with isolated ON or longitudinally extensive TM (LETM) or less commonly brain/brainstem disease are referred to as NMO spectrum disorders (NMOSD). However, many patients, who have overlapping features of both NMO and MS, test negative for AQP4-Abs and may be difficult to definitively diagnose. This raises important practical issues, since NMO and MS respond differently to immunomodulatory treatment and have different prognoses. Here we review distinct features of AQP4-positive NMO and MS, which might then be useful in the diagnosis of antibody-negative overlap syndromes. We identify discriminators, which are related to demographic data (non-white origin, very late onset), clinical features (limited recovery from ON, bilateral ON, intractable nausea, progressive course of disability), laboratory results (cerebrospinal fluid (CSF) pleocytosis with eosinophils and/or neutrophils, oligoclonal bands, glial fibrillary acidic protein in the CSF) and imaging (LETM, LETM with T1 hypointensity, periependymal brainstem lesions, perivenous white matter lesions, Dawson's fingers, curved or S-shaped U-fibre juxtacortical lesions). We review the value of these discriminators and discuss the compelling need for new diagnostic markers in these two autoimmune demyelinating diseases of the central nervous system.